La autolesión (cutting) y su relación con la autoestima en estudiantes del décimo año de la unidad educativa “Amelia Gallegos Díaz” de la ciudad de Riobamba, provincia de Chimborazo, en el periodo febrero- junio 2015 - Berrones Vallejo, Jéssica Marlene (2016)
The issue has relevance by pre-professional practices observed in the Educational Unit "Amelia Diaz Gallegos" there are students practicing self-harm (cutting), the overall objective states determine how self-injury is related to the self-esteem of students; we have conducted this investigation to establish whether there is a relationship of two variables or why students practice cutting, in the background research in the library of the Universidad Nacional de Chimborazo we found a thesis of self-esteem, we also have the foundations: philosophical, axiological, psychological, social and theoretical. The theory describes on self-esteem and cutting, the definition of terms, just as we use the operationalization of the variables used both dependent and independent variables to the investigation the inductive-deductive methods, analytic-synthetic were used, the type of research is not experimental the type of study is transversal. The survey and test to students were performed; the data was interpreted and analyzed. Finally, conclusions were drawn up and recommendations were proposed, the conclusion found that self- injury (cutting) it is related to self-esteem because there are students with low self- esteem and these young people are more likely to practice self-injury (cutting), as key recommendation we have to propose to teachers and psychologists to pay more attention to the adolescents' life and young people who need to unburden and do not find someone to talk about that emotional pain and they substitute it for physical pain.